In vitro Antioxidant, Lipoxygenase and Xanthine Oxidase inhibitory activity of fractions and macerate from Pandiaka angustifolia (vahl) Hepper - A.M.E. Thiombiano, Hilou Adama, Bangou Mindiédiba Jean, Bagora Bayala,Ouattara Nabèrè, Guenné Samson, Meda Nâg-Tiero Roland, Compaoré Moussa, Kiendrébeogo Martin, Millogo F. Jeanne and Nacoulma O. Germaine (Journal of Applied Pharmaceutical Science, 2014)
Pandiaka angustifolia (Vahl) Hepper, a species belonging to Amaranthaceae’s family is used in traditional medicine of Burkina Faso for the treatment of several diseases. The aim of this study was to evaluate the phenolics and flavonoids content, the antioxidant capacity, the lipoxygenase and xanthine oxidase inhibition potentials of Pandiaka angustifolia hydroacetonic macerate and fractions. Assay revealed that the Dichloromethane Fraction (DCMF) possess the best inhibitory activity of lipoxygenase, a key enzyme involved in inflammatory process with 83.84±1.89% of inhibition, as regards Xanthine Oxidase (XO) inhibiting percentage, n-hexane fraction (n-HF) exhibited the highest percentage of inhibition with 76.22 ± 4.78% at a concentration of 100µg/ml. Phenolics and flavonoids content in fractions and hydroacetonic macerate evaluation showed that hydroacetonic macerate possess the highest rate in total phenolic and the Dichloromethane fraction (DCMF) the highest rate in flavonoids content. This study showed that the apolar fractions of P. angustifolia is a potential natural source for the treatment of oxidative stress and inflammatory related diseases.
Keywords: Pandiaka angustifolia , antioxydant activity , LOX , XO, phenolic content.